Detecting Malicious Packet Dropping Using Traffic Patterns in MANET - Rao, Rajesh N.; Kesidis, George (Journal of Communication and Information Systems, 2017)
Ad hoc networks are gaining presence with the proliferation of cheap wireless devices and the need to keep them connected. Individual applications and larger missions. such as those of tactical sensor networks. require secure data transmission among wireless devices. Security remains a major challenge for such networks. Current protocols employ encryption and authentication techniques for secure message exchange. but given the limitations and innately insecure nature of ad-hoc networks. such mechanisms may not suffice. A security breach can. for example, be a network-level denial-of-service (DoS) attack, passive eavesdropping, or physical layer jamming to degrade communication channels. In a multihop network, an intruder node can degrade communication quality by simply dropping packets that arc meant to be relayed (forwarded). The network could then misinterpret the cause of packet loss as congestion instead of malicious activity. In this paper, we suggest that traffic transmission patterns be selected to facilitate verification by a receiver. Such traffic patterns are used in concert with suboptimal MAC that preserves the statistical regularity from hop to hop. This general technique for intrusion detection is therefore suitable for networks that are not bandwidth limited but have strict security requirements, e.g., certain kinds of tactical sensor networks.